2D Derivative Phase Induced Growth of 3D All Inorganic Perovskite Micro–Nanowire Array Based Photodetectors. (23rd June 2020) - Tong, Guoqing; Jiang, Maowei; Son, Dae‐Yong; Ono, Luis K.; Qi, Yabing
Abstract: A large number of derivative phases in inorganic perovskites are reported with special structures and extraordinary performances in photoelectronic device applications. The reverse phase transition between derivative phases and perovskites usually induces recrystallization or forms mixed components. In this work, derivative phase‐induced growth of the CsPbBr3 micro–nanowire (MW) array by utilizing phase transition of the 2D CsPb2 Br5 phase is reported. Owing to its layered structure and phase transition, annealing of CsPb2 Br5 at a temperature of 550 °C combined with solvent quenching leads to a templating effect to form a high‐quality CsBr MW array. Subsequent PbBr2 deposition and the second annealing are employed to form aligned CsPbBr3 MW arrays. Based on this method, a CsPbBr3 MW array‐based photodetector is fabricated. The large grain size, less grain boundaries, and lower surface potential of the CsPbBr3 MW array lead to high device performance with a responsivity of 7.66 A W −1, a detectivity of ≈10 12 Jones, and long‐term operational stability over 1900 min. Abstract : A well aligned CsPbBr3 micro–nanowire (MW) array is synthesized by controlling the growth of the intermediate CsBr MW array originated from the deposition of the 2D CsPb2 Br5 phase. Furthermore, a high‐performance photodetector is demonstrated based on the CsPbBr3 MW array.